Optimal Design for Placements of Tsunami Observing Systems to Accurately Characterize the Inducing Earthquake. Issue 24 (17th December 2017) - Mulia, Iyan E.; Gusman, Aditya Riadi; Satake, Kenji
Abstract: Recently, there are numerous tsunami observation networks deployed in several major tsunamigenic regions. However, guidance on where to optimally place the measurement devices is limited. This study presents a methodological approach to select strategic observation locations for the purpose of tsunami source characterizations, particularly in terms of the fault slip distribution. Initially, we identify favorable locations and determine the initial number of observations. These locations are selected based on extrema of empirical orthogonal function (EOF) spatial modes. To further improve the accuracy, we apply an optimization algorithm called a mesh adaptive direct search to remove redundant measurement locations from the EOF‐generated points. We test the proposed approach using multiple hypothetical tsunami sources around the Nankai Trough, Japan. The results suggest that the optimized observation points can produce more accurate fault slip estimates with considerably less number of observations compared to the existing tsunami observation networks. Key Points: Empirical orthogonal functions (EOFs) are used to identify effective locations of offshore tsunami measurements An optimization method based on a mesh adaptive direct search (MADS) is used to reduce the measurement points Smaller number (23 points) of better distributed locations than the existing network would produce slip distributions with smaller errors